Platelet-derived Growth Factor Receptor-beta is Differentially Regulated in Primary Mouse Pericytes and Brain Slices - Hutter-Schmid, Bianca; Humpel, Christian (Current Neurovascular Research, 2016)
Pericytes are perivascular cells and have heterogenous roles in the brain, such as controlling blood flow and entry of immune cells or regulating the blood-brain barrier. Platelet-derived growth factor (PDGF) receptor-beta (PDGFRβ) is highly expressed in pericytes, representing the most selective biomarker. The aim of the present study was to culture primary mouse pericytes and to determine the expression pattern by Western Blot as well as immunostainings. We will study the effects of different exogenous stimuli (such as transforming growth factor-β (TGFβ1), PDGF-BB, oxygendeprivation, beta-amyloid or serumfree conditions) on the different pericyte markers. Using Western Blot analyses, we show that PDGFRβ is selectively expressed in pericytes as a 160 kDa protein. Nestin, although not exclusively specific, is also expressed by pericytes, but markedly downregulated under serum-free conditions. PDGF-BB and oxygen-deprivation dramatically reduced PDGFRβ expression, while TGF1 increased its expression. The expression of PDGFRβ was intracellular as shown by confocal microscopy. Using Western Blot analyses, we demonstrate that pericytes also contain a 100 kDa PDGFRβ protein. However, in contrast to cortex brain slices, pericytes do not express a phosphorylated (Y740) isoform. Interestingly, PDGF-BB markedly reduced the 160 kDa isoform of PDGFRβ. In conclusion, our data show a detailed expression of different forms of PDGFRβ in primary pericytes, which is different to brain slices. However, we suggest that PDGFR is a highly selective marker for pericytes.
Keywords: platelet-derived growth factor-beta